ANALISIS STRATEGIK KINERJA GURU, EFEKTIVITAS PELATIHAN DAN KOMPENSASI FINANSIAL TERHADAP PRESTASI SISWA - BUDI ASIH; TABRONI YUSUF; IRVANDI GUSTARI (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2019)
Education has a strategic role because education is the key to a better life, the key to the progress of a nation. That is, a nation will progress if it continues to carry out learning activities to achieve progress. Reports from The Global Competitiveeness Report 2010 - 2011 show that education in Indonesia is below Thailand, Brunei Darussalam, Malaysia and Singapore. In Growth Competitiveness Index Indonesia ranks 44th out of 139 countries.The purpose of education is to improve the knowledge and expertise or skills of students, which will eventually give birth to the expected behavior and character.Even though it has been more than 50 years since Indonesia gained independence, the impact of national education has not been significant in building national character. There are still many educational problems that must be resolved, among others, the culture of corruption, injustice that causes poverty, consumerism and materialistic culture, environmental damage, the dangers of drugs, the decline in the quality of formal education, the rampant commercialization of education, and the low quality of human resources several developing countries.In order to improve the quality of the Indonesian nation, strategic and systematic steps are needed in planning, implementing, evaluating systems, and continually improving the Indonesian education system. Based on the conditions mentioned above, the authors are interested in examining several factors that affect the quality of human resources, namely the influence and significance of the effectiveness of training and Kompensasi Financial compensation on the performance of the teacher's impact on student achievement.